Polylingual behaviour of Vilnius youth: Searching for social identity - Vyšniauskienė, Inga (Kalbotyra, 2012)
The paper raises the problem of polilingual behaviour of Vilnius teenagers. The aim of this study is to reveal the frequency of linguistic features in the language of Vilnius teenagers of two age groups (13—14 and 15—17) as well as identify reasons for the informants’ polylingual behaviour. Extracts of spontaneous interactions from the corpus of the language of Vilnius youth have been chosen for the analysis. The results of the quantitative analysis have revealed that the elderly informants’ and younger boys’ polylingual behaviour is characterised by frequent, repetitive Russian features and nonrecurrent occurences of English features. The predominant use of English features in younger girls’ speech may imply that they have not yet mastered the Russian slang as well as point to their positive attitudes towards the English language. Within the framework of interactional sociolinguistics, the analysis of younger informants’ speech has revealed a link between English, German, Polish features and language play. Differently from the elderly teenagers, younger teenagers tend to change identities, e.g. an experienced player, an expert at love affairs, an adult who can evaluate youth language, via the play with English items. Russian items, which make a major part of slang in elderly teenagers’ speech, are used for sociopsychological purposes, as a means to display peer group identity. The study has revealed a varied polylingual production of Vilnius teenagers, which serves as a means of negotiating the social identity of a peer group member, creative and innovative teenager.